2015
DOI: 10.1002/pmic.201400297
|View full text |Cite
|
Sign up to set email alerts
|

Bovine sperm plasma membrane proteomics through biotinylation and subcellular enrichment

Abstract: A significant proportion of mammalian fertilization is mediated through the proteomic composition of the sperm surface. These protein constituents can present as biomarkers to control and regulate breeding of agricultural animals. Previous studies have addressed the bovine sperm cell apical plasma membrane (PM) proteome with nitrogen cavitation enrichment. Alternative workflows would enable to expand the compositional data more globally around the entire sperm's surface. We used a cell surface biotin-labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 78 publications
3
23
0
Order By: Relevance
“…Firstly, western blot analysis for TRPV1 expression was performed on both sperm plasma membrane and sperm cytoplasm isolated by differential centrifugation [28]. A protein signal corresponding to TRPV1 was mainly associated to isolated sperm membrane, characterized by a low representation of β-actin (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, western blot analysis for TRPV1 expression was performed on both sperm plasma membrane and sperm cytoplasm isolated by differential centrifugation [28]. A protein signal corresponding to TRPV1 was mainly associated to isolated sperm membrane, characterized by a low representation of β-actin (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Isolated sperm-plasma membrane were also obtained as previously described [28]. Briefly, cell pellet was suspended in hypotonic buffer and homogenized.…”
Section: Immunofluorescencementioning
confidence: 99%
“…For instance, it has been previously reported that the majority of plasma membranes of the disrupted spermatozoa heads are released in the form of unilamellar vesicles (13). These vesicles are typically pelleted by centrifugation at 285,000 ϫ g (13) and thus most probably are present in our seminal plasma samples prepared by centrifugation of semen at 13,000 ϫ g. Opening of such membrane vesicles and dissociation of intravesicular proteins requires high pH treatment, such as incubation with 100 mM Na 2 CO 3 at pH 11.6 (14). Thus, treatment of seminal plasma with guanidinium at pH 12 or deoxycholate at 63°C may lead to the release of TEX101 from such vesicles, making it available for ELISA measurements.…”
Section: Production Purification and Analysis Of Recombinant Human mentioning
confidence: 99%
“…The CMYA5 gene was pigs (Xu et al, 2011), due to the association of is a protein coding gene that may play an important role in the hydrolysis of circulating peptides. Kasvandik (2015), studying cattle sperm reported that this protein appears to be secreted to the cel termini of peptides in the plasma membrane, contributing to membrane modifications during sperm maturation; using immunocytochemistry, they is located mainly in the sperm middle and tail, suggesting its possi al. 2009 the amount of additive explained in percentage by windows of 10 adjacent SNPs.…”
Section: Me Carvalhomentioning
confidence: 99%
“…Accordingly, ectopically ber of melanoblasts and contribute to an , a member of the sideroflexin family and targeted to the mitochondrial membrane. In sheep, this gene and as important in the carrier molecule and related to gene was to the association of is a protein coding gene Kasvandik et al (2015), studying cattle sperm reported that this protein appears to be secreted to the cell termini of peptides in the plasma membrane, contributing to membrane modifications during sperm maturation; using immunocytochemistry, they is located mainly in the sperm middle and tail, suggesting its possible role al. 2009 In the ssGWAS analysis of ribeye area, several regions in the genome were associated with this trait; although the region of chromosome 4 explained most additive genetic variance; any candidate gene was observed in that region, which demands more studies about this region in the bovine genome.…”
Section: Me Carvalhomentioning
confidence: 99%